2011
DOI: 10.1111/j.1471-4159.2010.07014.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the NPC2 protein‐mediated cholesterol trafficking by membrane lipids

Abstract: J. Neurochem. (2011) 116, 702–707. Abstract Recycling and turnover of cell membranes play a critical role in cell metabolism. The internalization of membranes through the different processes of endocytosis, phagocytosis, and autophagy deliver a considerable amount of membranes and lipids to the endosomal and lysosomal system which is tasked with its degradation. Its failure to do so leads to severe fatal neurodegenerative diseases. In order to better understand how membranes are degraded, we have to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
0
39
0
3
Order By: Relevance
“…Several traffi cking pathways supply mitochondria with cholesterol from different sources, including endosomes. In previous work, we showed that MLN64 contrib- containing lysobisphosphatidic acid, which is present in internal membranes of endosomes, increase sterol transfer rates of NPC2, suggesting that NPC2 mobilizes endosomal cholesterol by transferring it from internal membranes to the endosome perimeter ( 15,16,18,19 ). In the absence of NPC2, cholesterol builds up in internal membranes and is not available for egress from the endosome.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Several traffi cking pathways supply mitochondria with cholesterol from different sources, including endosomes. In previous work, we showed that MLN64 contrib- containing lysobisphosphatidic acid, which is present in internal membranes of endosomes, increase sterol transfer rates of NPC2, suggesting that NPC2 mobilizes endosomal cholesterol by transferring it from internal membranes to the endosome perimeter ( 15,16,18,19 ). In the absence of NPC2, cholesterol builds up in internal membranes and is not available for egress from the endosome.…”
Section: Discussionmentioning
confidence: 90%
“…NPC1 is anchored in the late endosomal perimeter membrane by 13 transmembrane domains, forming three large loops in the endosomal lumen and a sterol-sensing domain with homology to several other proteins of cholesterol metabolism and regulation ( 14 ). NPC2 is a small, soluble sterol-binding protein in the endosome lumen, which mediates cholesterol transfer between membranes (15)(16)(17)(18)(19). According to a recent model, NPC1 and NPC2 interact to mediate the bulk of cholesterol egress from late endosomes by a mechanism in which NPC2 extracts cholesterol from inner membranes of late endosomes, binds to the second lumenal loop of NPC1, and transfers cholesterol to the N-terminal loop domain of NPC1 for distribution throughout the cell (20)(21)(22).…”
Section: Cholesterol Esterifi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…The resistance of BMP to the action of endolysosomal phospholipases is associated to its unusual sn1, sn1′ configuration. Negatively charged BMP, which stimulates most of the catabolic processes in the lysosome, is exclusively formed in the intravesicular membranes (6,13,51), but not in the lysosomal perimeter membrane, which seems to be quite resistant to lysosomal digestion. This is so because the perimeter membrane is protected by a thick glycocalix on its luminal leaflet from the attack by membrane-degrading enzymes present in the lumen of the lysosome (52)(53)(54)(55)(56).…”
Section: Glccer Hydrolysis Is Modulated By the Microenvironment Of Thmentioning
confidence: 99%
“…Flotillin and caveolins recruit other proteins to the raft, but they are structurally distinct (Allen, HalversonTamboli, Rasenick, 2007). The relative proportions of these components vary greatly depending on the cell and membrane type (Epand, 2008;Gallala, Breiden, Sandhoff, 2011). MLRs are specialized membrane structures that form an organized portion of the membrane with concentrated signaling molecules and links to the cytoskeleton (Byrum, Rodgers, 2015).…”
Section: The Concept Of Mlrs/nmda Receptorsmentioning
confidence: 99%